What is certain about uncertainty? - Garcia, Danilo Cascaldi et al (Journal of Economic Literature)
This paper provides a comprehensive survey of existing measures of uncertainty, risk, and volatility, noting their conceptual distinctions. It summarizes how they are constructed, their relative advantages in usage, and their effects on financial market and economic outcomes. The measures are divided into four categories based on the construction methodology: news-based, survey-based, econometric-based, and market-based measures. While heightened uncertainty is typically associated with negative real and financial outcomes, the magnitude of these effects and the interpretation of transmission channels crucially depend on identification considerations This paper thoroughly examines various measures of uncertainty, risk, and volatility. It highlights their conceptual differences and outlines how they are created, their relative benefits, and their impact on financial markets and economic results. These measures fall into four categories: news-based, survey-based, econometric-based, and market-based. While increased uncertainty usually correlates with adverse real and financial consequences, the extent of these effects and their interpretation hinge on identification factors..- Reproduced
Keywords: Uncertainty, Risk, Volatility, Measures, Construction methodology News-based Survey-based, Econometric-based, Market-based Identification, considerations